Urban Informal Workers : Representative Voice and Economic Rights - Chen, Martha; Bonner, Chris; Chetty, Mahendra; Fernandez, Lucia; Pape, Karin; Parra, Federico; Singh, Arbind; Skinner, Caroline (World Bank, Washington, DC, 2013)
This paper summarizesthe analysis of five case studies prepared for the 2013 World Development Report team that illustrate why and how the representative voice and economic rights of urban informal workers should be promoted: (1) the Self-Employed Women‘s Association of India; (2) the National Policy and Law for Street Vendors in India; (3) the Legal Cases for Street and Market Vendors in Durban, South Africa; (4) the Constitutional Court Judgments for Waste Pickers in Bogotá, Colombia; and (5) the Campaign for an International Convention on Decent Work for Domestic Workers. These case studies describe efforts to secure the livelihoods of urban informal workers by increasing their representative voice and their economic rights. In four of the five cases, the exception being the domestic workers case, organizations of these workers took the lead as partners in a global project called Inclusive Cities for the Working Poor. The lessons learned in regard to increasing voice and realizing rights are synthesized, with a focus on common strategies (including organizing, awareness building, advocacy, and legal struggles), common barriers and constraints (including an inappropriate or hostile institutional environment, competing vested interests, and the mindsets of influential stakeholders), and common sources of support (including pro-bono lawyers, activist academics, specialized non-governmental organizations, and, most importantly, alliances of organizations of informal workers).